1999
DOI: 10.1136/jnnp.67.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Extrapyramidal involvement in amyotrophic lateral sclerosis: backward falls and retropulsion

Abstract: Three patients with sporadic amyotrophic lateral sclerosis (ALS) presented with a history of backward falls. Impaired postural reflexes and retropulsion accompanied clinical features of ALS. Hypokinesia, decreased arm swing, and a positive glabellar tap were noted in two of these three patients. Cognitive impairment, tremor, axial rigidity, sphincter dysfunction, nuchal dystonia, dysautonomia, and oculomotor dysfunction were absent. Brain MRI disclosed bilateral T2 weighted hyperintensities in the internal cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 13 publications
0
36
0
2
Order By: Relevance
“…Mild parkinsonism is present in 5-15% of patients with ALS, and is typically characterized by postural instability and backward falls. 78,81 In such patients, abnormalities in the nigro striatal system can be seen on dopamine transporter imaging or at autopsy. 78,[81][82][83] In our experience, distinguishing the spastic, extrapyramidal and frontal motor findings in such patients is not trivial, which could explain why different studies have reported variable frequencies of ALS-parkinsonism.…”
Section: Als With Extrapyramidal Involvementmentioning
confidence: 99%
“…Mild parkinsonism is present in 5-15% of patients with ALS, and is typically characterized by postural instability and backward falls. 78,81 In such patients, abnormalities in the nigro striatal system can be seen on dopamine transporter imaging or at autopsy. 78,[81][82][83] In our experience, distinguishing the spastic, extrapyramidal and frontal motor findings in such patients is not trivial, which could explain why different studies have reported variable frequencies of ALS-parkinsonism.…”
Section: Als With Extrapyramidal Involvementmentioning
confidence: 99%
“…Symptoms and signs of parkinsonism have also been described in ALS [2,4,6,[10][11][12], with a frequency ranging from 5% to 17% [12][13][14]. ALS however is a distinct MND, which involves both upper and lower motor neurons-related symptoms and signs, and it shows a steadily clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapyramidal signs and symptoms due to nigrostriatal dysfunction have been reported in patients with Amyotrophic Lateral Sclerosis (ALS) [1][2][3][4][5]. However, outside the known ALS-Parkinson-Dementia complex (ALS-PD) of the Guam and Kii Peninsula of Japan, the comorbidity of Parkinson's disease and ALS is rare.…”
Section: Introductionmentioning
confidence: 99%
“…У части пациентов с БАС отмечаются признаки нечувствительного к леводопе мягкого синдрома пар-кинсонизма (с преобладанием постуральной неустой-чивости и падениями назад) [48]. Гораздо реже выявля-ется сочетание БАС с болезнью Паркинсона, отвечающей на терапию леводопой.…”
Section: том 7 Volunclassified